Energy transfer from fluorene-based polymers to single-walled carbon nanotubes - Chiang, Yi Wei. (2009)
In this report, we have examined the energy transfer effect from fluorene-based polymers namely, Poly[(9,9-dihexylfluorenyl-2,7-diyl)-co-(9,10-anthracene)], Poly(9,9-di{2-[2-(2-methoxy-ethoxy)ethoxy]ethyl}fluorenyl-2,7-diyl), Poly[(9,9-dioctylfl uorenyl-2,7-diyl)-co-(9-hexyl-3,6-carbazole)] and Poly(9,9-dioctylfluoreny- 2,7-diyl), to single-walled carbon nanotubes by using photoluminescence excitation spectroscopy mapping. Such energy transfer is a result from the excitons transfer of the polymer to the SWNTs and remitting of energy through photon due the band structure of semi-conducting SWNTs. The polymer and CoMoCat65 were dispersed in toluene to obtain single-walled carbon nanotubes. At low level of polymer concentration, it was observed that the optimal excitation wavelength on the PLE map has the same wavelength as the characteristic wavelength absorption of the polymer. As the concentration of the polymer in the solution increase, the optimal excitation wavelength on the PLE maps have also increase. This is likely due to the extended conformation of polymer on the surface of the SWNT. Lastly, we have also shown the structure of the polymer i.e. the backbone and the side chain, is a major factor that determine the interaction with the carbon nanotube in terms of solubility and also the selective of the SWNT species.